ADDRESS TERMS USED BY SUKU ANAK DALAM - MUTIARA, RICHA RACHMA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Address Terms, Orang Rimba, Bahasa Rimba.There are many ethnic groups in Indonesia which use specific languages. One of them is Suku Anak Dalam or called Orang Rimba. Suku Anak Dalam is a semi nomadic ethnic group living in National Park of Bukit Dua Belas, Jambi. They use Bahasa Rimba to communicate to each other. In Bahasa Rimba to address someone is the most important things to be considered. Bahasa Rimba has some variations and also has some social functions. The writer conducted a study about address terms used by Suku Anak Dalam by using Kridalaksana classification of address terms and Wardhaugh’s theory on the function of address terms. This study focuses on two problems: (1) What are the address terms used by Suku Anak Dalam, (2) What are the functions of address terms used by Suku Anak Dalam.This study uses qualitative approach to describe the address terms used in Bahasa Rimba and answer the problems. There are two types of data employed in this study, namely primary and secondary data. They are in the form of transcription of the observation result and in the form of transcription of interview result. Moreover, this study is a qualitative research because the writer only analyzed the data without any statistical number.This research finds 28 address terms used by Suku Anak Dalam which are classified into four categories; 4 terms in second personal pronouns, such as diria, mikae, senamo and urangmeru; 8 terms in kinship terms, such as induk, bepak, kakok, nenek jenton; 4 terms in title and rank categories, such as temenggung, bepak kepala adat, ibu guru; and also 12 terms in other categories, such as guding, bebet, kinde, waris and jenang. Furthermore, address terms used by Suku Anak Dalam has some social functions such as to show politeness, to show intimacy, to show solidarity, and to maintain social status.To summarize, address terms used by Suku Anak Dalam has some variations, by the title or rank, sex, age, etc. The address terms are used to address their family, their neighbor, the people around, their friends, their teacher, the people who already passed away, and even the stranger. The function of the address terms that is found in this study are to show politeness, intimacy, solidarity, and also to maintain social status. The writer also hopes that this study can provide better and deeper explanation especially on address terms in Bahasa Rimba. The writer suggests the next researchers who want to conduct a research about Bahasa Rimba focusing on different linguistic aspects such as, semantic,syntax, pragmatic, etc. for their research, so that their study is different and unique.